2010
DOI: 10.1007/s11523-010-0148-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapies for non-clear renal cell carcinoma

Abstract: The treatment of advanced and metastatic kidney cancer has been revolutionized by the development of targeted systemic therapies. Despite the growing number of available agents approved for use against clear cell renal cell carcinoma, patients with non-clear histologies, constituting approximately 1 in 4 cases of kidney cancer, have not received the same attention. The majority of clinical trials testing novel targeted therapies have excluded non-clear subtypes, providing limited therapeutic options for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…However, constitutive activation of HIF is also a characteristic of certain nonclear cell RCC subtypes (45)(46)(47)(48) even though VHL mutation is exceedingly rare in these tumors (49). Because VHL is functional in these subtypes, gramicidin A is likely to have therapeutic utility in this traditionally underserved patient population (8). Furthermore, gramicidin A may also prove effective in other cancers as upregulation of HIF occurs in the majority of solid tumors and generally correlates with poor survival (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, constitutive activation of HIF is also a characteristic of certain nonclear cell RCC subtypes (45)(46)(47)(48) even though VHL mutation is exceedingly rare in these tumors (49). Because VHL is functional in these subtypes, gramicidin A is likely to have therapeutic utility in this traditionally underserved patient population (8). Furthermore, gramicidin A may also prove effective in other cancers as upregulation of HIF occurs in the majority of solid tumors and generally correlates with poor survival (6).…”
Section: Discussionmentioning
confidence: 99%
“…are now routinely used for patients with ccRCC, and have succeeded in increasing progression-free survival and quality of life. However, these agents typically fail to achieve durable remission in most cases (7), and little is known about their utility for nonccRCC subtypes as these patients were excluded from clinical trials (8).…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib and sunitinib, which are broad-spectrum inhibitors of receptor tyrosine kinases (RTK) activated by HIF1 targets such as VEGF, PDGF, and TGFa, have been used in the treatment of sporadic papillary RCC with varying success. Somewhat more promising results have been obtained with mammalian target of rapamycin (mTOR) inhibitors [101]. Data about the specific response of HLRCC tumors to these molecules is unfortunately not available.…”
Section: Renal Cell Cancermentioning
confidence: 99%
“…This is congruent with other studies. 9 It seems natural that non-clear cell renal carcinoma takes on an alternate biochemical mechanism for tumour proliferation. Recent studies have suggested that the combination of gemcitabine and cisplatin provides an objectively good response for patients with CDC.…”
Section: 2mentioning
confidence: 99%